Analysis of Payroll Accounting Information System in Controlling Operational Costs at SMK PGRI 3 Bogor City - Komalasari, Andriyani Siti; Ningrum, N.ARumiasih.; Syukur, R. Dudung (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2023)
This research aims to analyze payroll accounting data for employees of SMK PGRI 3 Bogor City. The results of this research will help SMK PGRI 3 Bogor City in making decisions about the payroll system to use, as well as when to collect the necessary data. The data analysis technique used to achieve the research objectives is to compare theory with practice at SMK PGRI 3 Bogor City. This research uses a descriptive approach method at SMK PGRI 3 Bogor City with qualitative data types, which focuses on the payroll accounting information system at SMK PGRI 3 Bogor City and operational cost control at SMK PGRI 3 Bogor City, interview and documentation data collection methods, and analysis techniques qualitative data. Data analysis in this research begins by analyzing related functions, supporting documents, accounting records used, network procedures and internal controls. The results of this research indicate that the payroll accounting information system at SMK PGRI 3 Bogor City is good in theory and has been developed in accordance with theory so that it can provide accurate information regarding the payroll process as well as determining operational costs applied at SMK PGRI 3 Bogor City is good where the determination control of operational costs on payroll is determined by looking at the employee attendance system which already uses a fingerprint sensor system, so the salary costs that must be paid are more precise because attendance cannot be manipulated.